Model Strategi Pemasaran Pelatihan Kerja di UPT Balai Latihan Kerja Surabaya - Trisna Febi Nurlaili; Nurdina Rahmatika; Veny Juliarti (JURNAL RISET MANAJEMEN (JURMA), 2024)
Training marketing strategies are one way to introduce training institutions to the wider community. With the right targeted training marketing strategy, it can facilitate training institutions in carrying out promotions. This research is qualitative research using a case study aPProach. Data collection techniques include observation, documentation, and in-depth interviews. This study aims to identify the various training marketing strategy models employed by UPT BLK Surabaya, along with their strengths and weaknesses. The results of the study concluded that there are many marketing strategy models implemented by UPT BLK Surabaya to market their training programs, including 1) updating Instagram, 2) using the Simple Cak aPPlication, 3) socialization to local communities, 4) socialization to schools, and 5) conducting MTU training. Among these various marketing models, publication through Instagram is the most effective way to expand training information to the wider community.